AMELOBLASTOMA ASSOCIATED WITH DENTIGEROUS CYST - Ivanov, A.; Ivanov , G.; Bivolarski, I. (EurasianUnionScientists, 2021)
Ameloblastoma is a benign, locally aggressive tumour, with an unicystic variant that is very difficult to be differentiated from odontogenic cysts, because of their similarity in the clinical manifestation and X-ray examination. The morphological similarities between these processes make for a more difficult histological diagnosis. We present a case of a 32-year old male, admitted in the Maxillofacial surgery clinic in a University hospital for surgical treatment, because of a swelling in the left mandibular vestibule. A cystic formation, histologically diagnosed as an epithelial one, is removed. Eight months later, the patient is admitted once again, with the same symptoms. The biopsy result from the second operation is a plexiform unicystic ameloblastoma. What is being discussed is the connection between the two pathological processes and the difficulties with giving the correct morphological diagnosis.